PEMILIHAN PROGRAM STUDI AKUNTANSI DAN FAKTOR YANG MEMPENGARUHINYA - Aurelia Melinda Rayani; Daniel Pratama; Natalia Retno Ika Sundari (Jurnal Riset Akuntansi dan Keuangan, 2022)
ABSTRACT The emergence of an interesting phenomenon regarding the decline in the number of enthusiasts for accounting study programs in the midst of industry 4.0 is one of the interesting things for researchers. This is in contrast to the output of the accounting study program which produces accountants graduates who work in almost all sectors of the organization. The factors used in this study are attitudes, support, and behavioral control, and include job opportunities and institutional reputation as moderating variables. This exploration was designed using a four Likert scale questionnaire. Questionnaires were distributed using a google form based on convenience sampling. Furthermore, the questionnaire was processed using Warp-PLS. The conclusions of this study are (1) Attitude has a significant positive effect on the intention to choose the Accounting Study Program (2) Job opportunities are not able to moderate the influence of attitude on the intention to choose the Accounting Study Program (3) The reputation of the institution is not able to moderate students' attitudes towards the intention to choose the Accounting Study Program (4) Support has a significant positive effect on the intention to choose the Accounting Study Program (5) Behavioral control has a significant positive effect on the intention to choose the Accounting Study Program. Keywords: Career path, student perception, lecturer's role/ teacher’s roleABSTRAKMunculnya fenomena menarik mengenai penurunan jumlah peminat program studi akuntansi di tengah industri 4.0 menjadi salah satu hal yang menarik bagi peneliti. Hal ini berlawanan dengan output program studi akuntansi yang menghasilkan lulusan akuntan yang bekerja di hampir semua sektor organisasi. Adapun faktor-faktor yang digunakan dalam penelitian ini adalah sikap, dukungan dan kontrol perilaku, serta menyertakan kesempatan kerja dan reputasi institusi sebagai variabel moderasi. Eksplorasi ini didesain dengan menggunakan kuesioner empat skala likert. Kuesioner dibagikan dengan menggunakan google form berdasarkan convenience sampling. Selanjutnya kuesioner diolah dengan menggunakan Warp-PLS. Simpulan dari penelitian ini adalah (1) Sikap berpengaruh positif signifikan terhadap niat memilih Program Studi Akuntansi (2) Kesempatan kerja tidak mampu memoderasi pengaruh sikap terhadap niat memilih Program Studi Akuntansi (3) Reputasi institusi tidak mampu memoderasi sikap mahasiswa terhadap niat memilih Program Studi Akuntansi (4) Dukungan berpengaruh positif signifikan terhadap niat memilih Program Studi Akuntansi (5) Kontrol perilaku berpengaruh positif signifikan terhadap niat memilih Program Studi Akuntansi. Kata Kunci: Sikap, kesempatan. reputasi instituasi, dukungan, kontrol perilaku